2014
DOI: 10.1007/s10584-014-1278-x
|View full text |Cite
|
Sign up to set email alerts
|

Guilty conscience: motivating pro-environmental behavior by inducing negative moral emotions

Abstract: Conceptual frameworks in the realm of climate-related policy, attitudes and behavior frequently argue that moral emotions play a crucial role in mobilizing pro-environmental action. Yet, little is known about the direct impact of moral emotions on environmental attitudes and behavior. Drawing on emotion research in the context of intergroup relations, the current paper investigates the role of guilty conscience (guilt and shame) as well as other emotions (anger, sadness, pride, and emotional coldness) in motiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
137
1
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 200 publications
(162 citation statements)
references
References 47 publications
6
137
1
3
Order By: Relevance
“…The current study is the first to show that personal feelings of pride are related to one's own engagement in pro-environmental behavior; previous work has only demonstrated that feedback about an in-group's behavior invokes a feeling of pride (Harth et al, 2013). The current study is also the first to demonstrate that findings about the relationships between pride and guilt and pro-environmental behavior generalize outside of an experimental setting (see Harth et al, 2013;Mallett et al, 2013;Rees et al, 2015) to people's experiences as they live their daily lives.…”
Section: Pride and Guilt As Outcome Variablesmentioning
confidence: 49%
See 3 more Smart Citations
“…The current study is the first to show that personal feelings of pride are related to one's own engagement in pro-environmental behavior; previous work has only demonstrated that feedback about an in-group's behavior invokes a feeling of pride (Harth et al, 2013). The current study is also the first to demonstrate that findings about the relationships between pride and guilt and pro-environmental behavior generalize outside of an experimental setting (see Harth et al, 2013;Mallett et al, 2013;Rees et al, 2015) to people's experiences as they live their daily lives.…”
Section: Pride and Guilt As Outcome Variablesmentioning
confidence: 49%
“…The low guilt experienced by participants could arise for a number of reasons: The lack of pro-environmental action during any small period of time might not be enough to make most people experience more than weak feelings of guilt in relation to their environmental behavior. As suggested by previous research (Harth et al, 2013;Mallett, 2012;Mallett et al, 2013;Rees et al, 2015), perhaps feedback on lack of action over a longer period of time or about larger, more impactful behaviors is required to elicit feelings of guilt that are strong enough to trigger subsequent action. Another possibility is that in the course of their day, perhaps people find other ways to alleviate their guilt and this releases them from the need to take reparative action by engaging in subsequent pro-environmental behavior.…”
Section: Subsequent Pro-environmental Behavior As Outcome Variablementioning
confidence: 85%
See 2 more Smart Citations
“…Importantly, the relationship between ecological attitudes and environmental protection behavior was verified by Ramkissoon et al [11], Rees, Klug, and Bamberg [12], and others who demonstrated that ecological emotion and ecological attitudes were significantly related to actual ecological protection. The research on ecological attitudes by Fraj and Martinez [13] and others, that investigate attitudes in terms of elements, divide ecological attitudes into three dimensions: cognition, emotion, and intention.…”
Section: Literature Review and Proposed Hypothesesmentioning
confidence: 84%